Probability models of wear process - Сорокатый, Р. В.; Писаренко, В. Г.; Дыха, М. А. (Problems of Tribology, 2014)
The probability model of a wear as systems with reservation that has allowed to explain the fact enough the durable period of functioning of system as a whole, at rather low wear resistance separately the taken frictional contact is constructed // Problems of Tribology. – 2011. – № 1. – P. 114-119